PEMANFAATAN TEKNOLOGI BIOPORI UNTUK MENINGKATKAN DERAJAT KESEHATAN LINGKUNGAN DI DESA BULUHCINA KECAMATAN SIAK HULU, KABUPATEN KAMPAR (Jurnal Dinamika Pengabdian, 2020)
Buluhcina Village, Siak Hulu Subdistrict, Kampar Regency is located on the banks of the Kampar river. Flood occurs almost every year so that pools of water are formed. The behavior of the people of Buluhcina Village in processing the organic waste they produced remain poor. Therefore, there must be a way to overcome it by applying biopori technology in Buluhcina Village, Siak District, Kampar Regency. Counseling activities and training on household waste management were held in the Buluhcina Village Hall, Siak Hulu District, Kampar Regency on October 5th, 2019. The activity was attended by 16 participants. The result showed the increases the level of knowledge about organic household waste management after counseling, from 55.69 ± 10.216 to 72.44 ± 12.101 (p